MEDICAL POLICY OF THE STATE AS AN OBJECT OF PUBLIC ADMINISTRATION - Bakumenko V. D.; Popov S. A.; Voshko I. В. (Pressing Problems of Public Administration, 2021)
The medical policy of the State, as an object of public management and administration, as one of the important functions of the State regarding the proper maintenance, functioning and development of the Ukrainian society is considered. This function is realized through normative and legal regulation of the complex State mechanism of State policy management in the country (medical sector). This mechanism is universal for the implementation of all types of policies, based on constitutional and regulatory principles, non-State and State mechanisms. The latter is dominated by the mechanism of public administration and the political process. The structure of the policy management mechanism is correlated with the stages of the political process; accordingly divided into mechanisms for policy formation, political and legal decision-making and policy implementation. Each of these mechanisms combines State and non-State mechanisms. The main subjects of State policy are the Verkhovna Rada of Ukraine (approves State programs), the Cabinet of Ministers of Ukraine (approves the Concepts of these programs) and sectoral ministries: directly develop and implement programs, including health care programs. The policy management mechanism is formed by regulatory principles and includes: main subjects and their authority (defined by the Constitution of Ukraine); principles, priorities, types and spheres of policies, competencies and powers of its main subjects (determined by the principles of domestic and foreign policy); tasks, competencies, authorities (of the Cabinet of Ministers of Ukraine, central executive bodies), regulations, provisions, methodology, procedure, other principles of the political process. Analysis of the program for the development of primary health care shows the presence of shortcomings. At present, the use of State strategic management methods by executive bodies is approved. These methods are appropriate and require further research.